2018
DOI: 10.15406/emij.2018.06.00201
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and heart mitochondrial nitric oxide under hypovolemia

Abstract: After 28 days of treatment, the animals were anesthetized with urethane (1 g/kg ip). A tracheotomy was performed using polyethylene AbstractThe aim of the present work was to examine the effect of thyroid state on rat heart mitochondria function during hypovolemia. Sprague-Dawley rats treated with T 3 (hyper, 20 μg/100 g body weight) or 0.02% methimazole (hypo, w/v) for 28 days. Hypovolemia was induced by acute hemorrhage. O2 uptake, complex I activity and mitochondrial nitric oxide synthase (mtNOS) protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…We demonstrated that decreased TH level would probably be a hormonal environment that promotes changes in mitochondrial NO bioavailability modulating oxygen consumption and cell respiration. Alterations of complex I activity could mediate these effects (Ogonowski et al, 2018). We suggest that these mitochondrial alterations associated with thyroid disorder may be responsible for On the other hand, besides their function in energy conversion, mitochondria participate in multiple metabolic pathways, such as the urea cycle, the metabolism of amino acids and lipids, and the biogenesis of haem and iron sulfur clusters (Smith et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We demonstrated that decreased TH level would probably be a hormonal environment that promotes changes in mitochondrial NO bioavailability modulating oxygen consumption and cell respiration. Alterations of complex I activity could mediate these effects (Ogonowski et al, 2018). We suggest that these mitochondrial alterations associated with thyroid disorder may be responsible for On the other hand, besides their function in energy conversion, mitochondria participate in multiple metabolic pathways, such as the urea cycle, the metabolism of amino acids and lipids, and the biogenesis of haem and iron sulfur clusters (Smith et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…We demonstrated that decreased TH level would probably be a hormonal environment that promotes changes in mitochondrial NO bioavailability modulating oxygen consumption and cell respiration. Alterations of complex I activity could mediate these effects (Ogonowski et al., 2018 ). We suggest that these mitochondrial alterations associated with thyroid disorder may be responsible for cardiovascular alterations.…”
Section: Discussionmentioning
confidence: 99%